Land suitability classification for millet production in Katsina State, Northwest, Nigeria - Abdullahi, Sani; Ismail, Roslan; Zaibon, Syaharudin; Ahmad, Nordin; Noma, Samaila Sani (WJIR, 2021)
Land suitability is a function of soil characteristics and crop requirement. It involves the evaluation and grouping of specific areas of land in terms of their suitability for defined agricultural use. Factors such as soil characteristics, climatic condition, topography (terrain), rainfall, erosion etc. Henceforth, matching the land characteristics with the crop requirements provides suitability index in the form of ranks which are fundamental for sustainable agricultural practices. The main objective of the research was focused on GIS techniques for land suitability assessment and subsequently determine physical-chemical-climatic risk (to improve millet yield) in millet production for sustainable farming. This paper presents the land suitability for millet production in Katsina State (Nigeria). A total of fifty-five (55) soil samples were collected at the depth of 0-30cm, air-dried, gently crushed, and sieved through 2mm for soil physical-chemical analyses. Soil samples coordinates were marked with GPS Garmin 60csx and subjected to geospatial distribution analysis. Data collected for climatic (rainfall and temperature) condition and analyzed for soil physio-chemical characteristics were subjected to descriptive statistics (SAS v9.4). Soil properties distribution map were generated with ArcGIS v10.3 using Inverse Distance Weighted (IDW) techniques. The suitability for millet cultivation in Katsina from the climate and physical-chemical parameters indicates that annual rainfall (604-702mm), elevation (434.75-558.5◦), temperature (26.50-26.99◦C), drainage, erosion, soil depth (0-30cm), soil pH (6.4-6.7), organic carbon (OC, 1.67-2.22%) and organic matter (OM, 0.2-3.0%), and phosphorus (P, 4.40-10.23%) are noted within the acceptable suitability index values (for Class S1 to Class S3), that represent sustainable crop production. While, cation exchange capacity (CEC, 5-15 cmol(+)/kg), total nitrogen (TN, 0.5-5.0%), exchangeable acidity (EC,0.03-0.65ds/m) and effective sodium percentage (ESP, 1.06-1.53%) were noted below average value for crop production. Land suitability Class S1 (highly suitable) covers 1328.40ha which is about 21.19% of the study area. While land suitability Class S2 (moderately suitable) covers 1098ha (17.53% area). The land suitability Class S3 cover 1767ha (28.19% area). Besides that, Class N1 (potentially not suitable) covers about 851.33ha (13.58% area) and, finally Class N2 (potentially and actually not suitable) covers about 1223.08ha (19.51% area) with scores below average of millet requirement. Further, the Class N2 areas marked with rock outcrop and inherent low fertility. Studied area (Katsina) suitability class for crop production as follow: S3>S1>N2>S2>N1. This indicates that, land area under Class S3 (28.19%) requires moderate level of soil amendment to improve millet production. Whereas, Class S2 (17.53%), requires minimal level of soil amendment, whereas Class N1 and N2 with total land area of percentage of 30.09%, requires high input of soil amendment. Therefore, it can be stated that different land unit requires different level of input and land management to facilitate (improve) millet production in Katsina state for sustainable crop production.